2018
DOI: 10.1177/1350650118774132
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion and tribological behaviour in a 3.5% NaCl solution of vacuum arc deposited ZrCN and Zr–Cr–Si–C–N coatings

Abstract: ZrCN and Zr–Cr–Si–C–N coatings were deposited on Si (100) and 316L stainless steel substrates using the cathodic vacuum arc technique in a mixed atmosphere of C2H2 and N2. The coatings were grown keeping almost constant the ratio of the C2H2 and N2 mass flow rates, substrate bias and deposition temperature at ∼0.81, −200 V and 320 ℃, respectively. The investigation carried out aimed to determine the corrosion and tribological performance of the novel Zr–Cr–Si–C–N coating obtained by Cr and Si addition to the Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 83 publications
1
4
0
Order By: Relevance
“…8.8 at.%. It can also be seen that, as intended, the (C+N)/(metal+Si) ratio was in the range TiNbCN coatings [33]. This increase may be ascribed to the lattice distortion as a result of adding Si into the coating matrix.…”
Section: Elemental and Phase Compositionssupporting
confidence: 67%
See 1 more Smart Citation
“…8.8 at.%. It can also be seen that, as intended, the (C+N)/(metal+Si) ratio was in the range TiNbCN coatings [33]. This increase may be ascribed to the lattice distortion as a result of adding Si into the coating matrix.…”
Section: Elemental and Phase Compositionssupporting
confidence: 67%
“…The coatings were deposited in a mixture of CH 4 and N 2 reactive gases, using a cathodic arc system, equipped with two cathodes made of Zr (99.99% purity) and Ti85 at.%-Nb15 at.% or Ti88 at.%-Si12 at.%, respectively. Details of the deposition system may be found in [43]. The targets were supplied by Cathay Advanced Materials Limited, Guangdong, China.…”
Section: Methodsmentioning
confidence: 99%
“…The coatings were prepared using both CH 4 and N 2 as reactive gases (99.999% purity, Linde). The position of each cathode inside the deposition chamber was the same as those described in [33]. In order to guarantee the uniform thickness of the coatings, the substrate holder was rotated by 15 rot/min.…”
Section: Coatings Preparationmentioning
confidence: 99%
“…For medical applications, however, they have not yet been tested. Nevertheless, an alternative solution was the addition of Zr and Cr to the Si-N and Si-C-N matrix for severe wear and corrosive applications [33].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, recent work performed by L.R. Constantin et al [18] presented a correlation between the structures, tribological properties and corrosion of Zr-Cr-Si-C-N coatings. They showed that the improvement of microstructure by the formation of carbides, as well as friction, wear and anti-corrosive performance of Zr-C-N and Zr-Cr-Si-C-N coatings was achieved by the presence of C-Metal, N-Metal, C-C and N-C chemical bonds.…”
Section: Introductionmentioning
confidence: 95%